Growth Response of Indian Major Carps Catla catla and Labeo rohita to Formulated Diets Containing Leaf Powders as Protein Source - S.K., Das; J.K., Manissery; T.J., Varghese (Fishery Technology, 2025)
Search for alternative sources of protein for partial or complete replacement o fishmeal is an ongoing process, since fishmeal, which is used as the major source of protein in pelleted feed, is becoming very expensive and scarce. In the present study fishmeal was partly replaced with locally available plant leaf powders, Eichhornia crassipes (pellet E) Colocasia esculenta (pellet C) and Gliricidia maculata (pellet G) and the pelleted feeds prepared separately were fed to the Indian major carps Catla catla and Labeo rohita and the growth performance was compared with fishmeal based control diet (pellet FM) for a period of 112 days. The best growth of catla was recorded in pellet FM followed by pellet C, E and G treatments, respectively. However, rohu registered maximum growth in pellet C followed by pellet G, E and FM treatments during the experimental period.